A new VPO catalyst for a sustainable environment. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2009)
Catalysis plays a central role in the development of sustainable processes, which are of primary importance to allow the present and future worldwide production and use of energy and chemicals while avoiding negative consequences to the environment. Future global prosperity will depend on new or improved processes that are economically and environmentally sustainable. Furthermore, the development of new catalysts and catalytic processes can open up to new selective chemical processes which may lead to a considerable reduction of undesired by·products or waste products. Selective catalytic oxidation is one of the major areas in industrial chemical production.